Genotyping of Mycobacterium tuberculosis isolates from alow-endemic setting in northwestern state of Paraná in Southern Brazil - Noguti, Erika Noda; Leite, Clarice Queico Fujimura [UNESP]; Malaspina, Ana Carolina [UNESP]; Santos, Adolfo Carlos Barreto [UNESP]; Hirata, Rosário Dominguez Crespo; Hirata, Mario Hiroyuki; Mamizuka, Elsa Massae; Cardoso, Rosilene Fressatti (Instituto Oswaldo Cruz, Ministério da Saúde, 2010)
The purpose of this study was to provide information about the genetic diversity and prevalent genotype of Mycobacterium tuberculosis in a low-endemic setting in northwestern state of Paraná in Southern Brazil. We employed spoligotyping and mycobacterial interspersed repetitive units-variable number tandem repeat (MIRU-VNTR) techniques to genotype M. tuberculosisisolates from patients with pulmonary tuberculosis (TB). The 93 isolates analyzed by spoligotyping were divided into 36 different patterns, 30 of which were described in the SITVIT database. Latin American and Mediterranean, Haarlem and T families were responsible for 26.9%, 17.2% and 11.8% of TB cases, respectively. From the 84 isolates analyzed by MIRU-VNTR, 58 shared a unique pattern and the remaining 26 belonged to nine clusters. The MIRU loci 40, 23, 10 and 16 were the most discriminatory. A combination of MIRU-VNTR and spoligotyping resulted in 85.7% discriminatory power (Hunter-Gaston index = 0.995). Thus, combining spoligotyping and MIRU-VNTR typing proved to be most useful for epidemiological study in this low-endemic setting in Southern Brazil. The current study demonstrated that there is significant diversity in circulating strains in the city of Maringá and the surrounding regions, with no single genotype of M. tuberculosispredominating.
Keywords: Mycobacterium tuberculosis; tuberculosis; molecular epidemiology; spoligotyping; MIRU